PENERAPAN MANAJEMEN BAHAYA HEWAN LIAR : PENCEGAHAN BAHAYA HEWAN LIAR DALAM MENUNJANG KESELAMATAN PENERBANGAN DAN PENYELESAIAN MASALAH PENGENDALIAN HEWAN LIAR - Dian Dwi Indriyani; Azzahra, Nadia Shifa; Dwi Afriyanto (Yayasan Nuraini Ibrahim Mandiri, 2024)
Previous research and related research are very important in a research paper and academic paper. Previous or related research serves to strengthen theories and phenomena regarding the relationship and influence between variables. This article discusses the factors that influence Wild Animal Hazard Management, namely Wild Animal Hazard Prevention in Support of Aviation Safety, and Wild Animal Control Problem Solving. The purpose of this article is to propose hypotheses regarding the influence between variables that will be used in further research. The results of this literature review article are: 1)Prevention of Wild Animal Hazards in Supporting Aviation Safety affects the Application of Wild Animal Hazard Management which aims to reduce the risk of a)attack or disturbance from wild animals; b).screening; c)evaluating while still preserving their population; d)minimizing conflicts between humans and wild animals; 2) Wild Animal Control Problem Solving affects the Application of Wild Animal Hazard Management which requires a series of actions and strategies to address situations when wild animals pose a threat or hazard to people and human activities. Keywords: implementation, prevention, and problem solvin